Impact of print-on-demand on academic books - Wilson-Higgins, Suzanne (Chandos information professional series., 2017)
The convergence of online book selling, digital printing, digital document workflow management and the computerization of small parcel logistics created a unique opportunity to create a viable commercial model for printing and supplying books on demand. This innovation was swiftly embraced by the academic publishing community heralding the rescue of the languishing academic monograph. The possibilities captured the imagination of creative academic and niche publishers enabling custom publishing, student editions of monographs, self-compiled wiki books and even the establishment of new university presses and open access publishers. The Impact of Print on-Demand on Academic Books takes an in-depth look at this phenomenon by looking back on two decades of innovation, reviewing the present state of academic publishing with respect to works being printed on demand and compiling the current forecasts and speculation about the future of academic and niche publishing given the impact of print on-demand.